2019
DOI: 10.1111/hex.12888
|View full text |Cite
|
Sign up to set email alerts
|

Frameworks for supporting patient and public involvement in research: Systematic review and co‐design pilot

Abstract: Background Numerous frameworks for supporting, evaluating and reporting patient and public involvement in research exist. The literature is diverse and theoretically heterogeneous. Objectives To identify and synthesize published frameworks, consider whether and how these have been used, and apply design principles to improve usability. Search strategy Keyword search of six databases; hand search of eight journals; ancestry and snowball search; requests to experts. Inclusion criteria Published, systematic appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
650
0
15

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 544 publications
(739 citation statements)
references
References 89 publications
12
650
0
15
Order By: Relevance
“…This will ensure that the modified MRT identified in this study can be fully evaluated and modified further if necessary. However, regardless of which approach is adopted to underpin PEI in research, evidence from this evaluation concurs with other studies which conclude that PEI should always be underpinned by procedures which ensure that participants receive ongoing and tailored guidance and support throughout the process [45][46][47].…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…This will ensure that the modified MRT identified in this study can be fully evaluated and modified further if necessary. However, regardless of which approach is adopted to underpin PEI in research, evidence from this evaluation concurs with other studies which conclude that PEI should always be underpinned by procedures which ensure that participants receive ongoing and tailored guidance and support throughout the process [45][46][47].…”
Section: Resultssupporting
confidence: 80%
“…The field of PEI therefore needs to expand who and how it recruits to PEI roles. A systematic review of frameworks designed to support PEI in research [47] grouped frameworks into five categories: power focused, priority setting, study focused, report focused and partnership focused. None of the frameworks could be categorised as having a personal development or social impact focus for the individuals who contribute to PEI in research or the broader public.…”
Section: Discussionmentioning
confidence: 99%
“…To address the need for means of determining the “return on engagement,” the aim of this paper was to scope, review and summarize the literature on monitoring and evaluation of patient engagement. Many publications present useful guidance for conducting patient engagement and assessing the quality . Evaluation studies focus mainly on qualitative methods and only occasionally link to specific outcomes .…”
Section: Introductionmentioning
confidence: 99%
“…User involvement is progressively becoming a routine element of health service research and is increasingly a common requirement for research funders . Although the importance of involving patients and the public in health‐care research is recognized, reviews of the literature find that users' roles are more often consultative than collaborative .…”
Section: Introductionmentioning
confidence: 99%
“…The designation ‘co‐production’ has been used in recent health service literature as a key factor in discussions of equity and partnership INVOLVE defines co‐production as ‘an approach in which researchers, practitioners and the public work together, sharing power and responsibility from the start to the end of the project, including the generation of knowledge.’ In this definition, power is depicted as the ‘holder’ of equity by constructing user involvement as a question of sharing power and influence. Several guidelines focus on issues related to partnership and power‐sharing in user involvement in research in an attempt to address the challenges which have been identified within user involvement in research . However, even though co‐production is portrayed as desirable, it is also described as utopian …”
Section: Introductionmentioning
confidence: 99%